Metabolic profile evolution in relapsed/refractory B-cell non-Hodgkin lymphoma patients treated with CD19 chimeric antigen receptor T-cell therapy and implications in clinical outcome - Serena De Matteis; Laura Del Coco; Federica De Castro; Anna Maria Giudetti; Beatrice Casadei; Francesco Iannotta; Francesco De Felice; Enrica Tomassini; Francesca Vaglio; Maria Naddeo; Irene Salamon; Gianluca Storci; et al. (Haematologica)
Plasma metabolomics analysis was performed on 44 patients with relapsed/refractory B-cell non-Hodgkin lymphoma (r/r/B-NHL) infused with approved CD19.CAR-T cell products at the time of pre-lymphodepletion (PLD) and at day +1, +7, and +30 after CAR-T cell infusion. At the PLD time point, a metabolic profile characterized by high lipoproteins and lactate and low glucose contributed to poor outcome prediction in association with high lactate dehydrogenase levels. At day+1, higher plasma levels of lipid metabolism products and lower glucose and glycoproteins levels were observed in tisa-cel compared to axi-cel-treated patients. At day+30, discriminant analysis found two clusters in a subgroup of patients, one with CR lasting one year after therapy, and another who relapsed within one year (relapsed>D30). This latter showed a higher content of N-GlycA, a known biomarker of systemic inflammation that is also correlated with C-reactive protein in our case setting of relapsing patients. Our data show complex metabolomic changes that track the evolution of the disease and drug activity in the first 30 days of CAR-T cell therapy. Conceivably, a pro-inflammatory drift may be linked to a forthcoming disease relapse in CAR-T patients.